Brothers in Arms in the European Car Wars: Employment Pacts in the EU Automobile Industry - Zagelmeyer, Stefan (Industrielle Beziehungen - Zeitschrift für Arbeit, Organisation und Management, 2001)
During the 1990s, company or plant-level collective agreements on employment and competitiveness were forged at most car producers in the European Union. In brief, these pacts aim at maintaining or creating jobs and at improving the competitiveness of the plant or company in inter- as well as intracompany competition. This paper first presents two approaches to analyse such employment pacts. It then introduces selected cases of company-level employment pacts in the European car industry. The main part of the paper analyses these employment pacts and discusses their implications for labour relations. The author concludes that these pacts may not just be seen as examples of concession bargaining, but rather as emerging forms of cooperative labour relations, which are about adjusting the governance of the employment relationship to the imperatives of joint competitive succes